MAKNA TPENAN MAN NAI MUTI DALAM TRADISI SUKU SANAK DAN PENGARUHNYA TERHADAP PERTUMBUHAN IMAN AKAN SAKRAMEN EKARISTI DALAM TERANG ENSIKLIK ECCLESIA DE EUCHARISTIA - Us'sanak, Aurelia; Benitius Metom, Philipus; Tae Mau, Lusius (Kanisius, 2025)
The purpose of this writing is to find out the meaning of the Tpenan Man Nai Muti tradition, the purpose of Tpenan Man Nai Muti, the values ??contained in the Tpenan Man Nai Muti tradition, the benefits of the Tpenan Man Nai Muti tradition, and to find out its influence on the growth of faith in the sacrament The Eucharist in the light of the encyclical Ecclesia de Eucharistia. The research method uses qualitative methods. Data collection techniques in this method are observation, interviews and documentation as the main tools for collecting data. In this research, almost all Sanak people believe that carrying out the Tpenan Man Nai Muti tradition will have a good influence so that it is always carried out every year. So it can be seen that in real life Tpenan Man Nai Muti has a very important role in the lives of the Sanak tribe people. From there, it can mean that as a cultured and godly society, people are taught to always instill an attitude of trust in the Creator and carry out traditions handed down by their ancestors. Tpenan Man Nai Muti is a traditional stage process in a series of ceremonies that are very important for the life of the Sanak tribe to express gratitude, ask for blessings and obtain sustenance. The Tpenan Man Nai Muti tradition is deeply rooted in the Sanak tribe and is a traditional ceremony every year to present a white rooster to Uis Neno. In this ceremony, previously the Sanak tribe people brought their harvests in the form of rice, corn and tourists to tah fe'u together at the traditional house. So the solution that must be taken to overcome the influence of the growth of faith in the sacrament of the Eucharist is to hold family pastoral visits for people who are less aware and active in activities in the Church, provide catechesis or family formation and pastoral catechesis for people or the community